Generalized Fuzzy c -Means Clustering and its Property of Fuzzy Classification Function - Kanzawa, Yuchi; Miyamoto, Sadaaki (Journal of advanced computational intelligence and intelligent informatics, 2021)
This study shows that a generalized fuzzy c -means (gFCM) clustering algorithm, which covers both standard and exponential fuzzy c -means clustering, can be constructed if a given fuzzified function, its derivative, and its inverse derivative can be calculated. Furthermore, our results show that the fuzzy classification function for gFCM exhibits a behavior similar to that of both standard and exponential fuzzy c -means clustering.